THE ROLE OF EMPLOYEE CREATIVITY AS A MEDIATOR BETWEEN HIGH-PERFORMANCE WORK PRACTICE, INNOVATIVE BEHAVIOR, AND SUSTAINABLE COMPETITIVE ADVANTAGE IN THE HOTEL INDUSTRY - Sarfilianty Anggiani; Tiurida Lily Anita (Fakultas Ekonomi dan Bisnis Universitas Padjadjaran, 2021)
This study aims to find if employee creativity has a significant impact as a mediator to High-performance work practice, innovative behavior, and sustainable competitive advantage in the Hotel industry during the pandemic. This study was conducted by conducting observations and surveys to Four Stars Hotels around the Jakarta area. Population and samples were taken from employees who work in the Four stars Hotel since the hotel was started operating again around December 2020. This research was conducted in a quantitative approach. The data collection instrument using a questionnaire with a sampling technique is purposive sampling. The analysis technique, namely path analysis using SMART PLS, is carried out to show whether employee creativity has an impact as a mediator to high-performance work practice, innovative behavior, and sustainable competitive advantage. The result shows that Employee creativity has an impact as a mediator to high-performance work practice, innovative behavior, and sustainable competitive advantage. Innovative behavior has no direct impact on sustainable competitive behavior.